Does the Application of International Classification of Disease Codes for the Cause of Death on Death Certificates Reduce Garbage Codes? - Park, Soobeom; Kim, Sun Hyu (Inquiry (00469580), 2022)
Introduction: This study aimed to determine if applying International Classification of Diseases (ICD) disease codes directly as the cause of death (COD) on death certificates (DCs) instead of writing or typing the COD could reduce the use of garbage codes. Methods: Beginning in April of 2016, a documentation process change was made, retiring the process of hand-writing or typing the COD onto DCs to directly applying ICD disease codes that were registered during the patient's course of treatment. The DCs issued at the emergency department (ED) 1 year before (Pre-code group) and after (Code group) applying ICD disease codes directly on DCs was instituted were retrospectively analyzed. The occurrence of garbage codes along with other major and minor errors was compared between the two groups. The investigation and judgment of errors were performed by four emergency physicians. Results: The overall garbage code occurrence in the Code group (25%) was significantly lower than that in the Pre-code group (49%). Fewer garbage codes were used in the Code group with an average of.5 in the Pre-code group and.3 in the Code group. No significant difference was identified in major error occurrences except for in the garbage codes. Minor errors were more common in the Pre-code group than in the Code group. Conclusion: The overall use of garbage codes on DCs could be reduced by changing the process by which physicians complete DCs, that is, the application of documenting ICD disease codes directly as the COD on DCs.